Discovery Learning-Based E-Book for Elementary School Science Learning - Gloria, Paula Ni Komang Axelina; Kristiantari, Maria Goreti Rini; Anzelina, Dewi (Universitas Pendidikan Ganesha, 2025)
The implementation of 21st-century education requires teachers’ creativity in designing learning activities that integrate appropriate media, instructional design, and assessment. However, in practice, many schools have not yet optimally integrated digital learning tools. This study aims to describe the design, product quality, and effectiveness of a Discovery Learning-based e-book on the topic of animal life cycles in the Natural and Social Sciences (IPAS) subject for fourth-grade elementary students. The research involved 28 fourth-grade students as participants. The method used was Research and Development (R&D) with the ADDIE model, consisting of five stages: analyze, design, development, implementation, and evaluation. Data were collected through questionnaires and tests. The findings reveal that: (1) the e-book was systematically and structurally designed following the ADDIE model; (2) the quality of the Discovery Learning-based e-book was rated “very good” by content experts (92.86%), instructional design experts (95.45%), and media experts (94.32%). Individual and small group trials also showed highly satisfactory results, each achieving 100%; (3) analysis of pretest and posttest data using the t-test indicated that the tvalue (7.213) was higher than the ttable value (1.703) at a 5% significance level, confirming a significant improvement in students’ learning outcomes after using the e-book. Based on these findings, it can be concluded that the Discovery Learning-based e-book is effective for use in IPAS learning for fourth-grade students and supports improved understanding of the animal life cycle. The study also highlights the practical implications of e-books as effective learning media in elementary education.